2008
DOI: 10.1055/s-2008-1038920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Intra-Abdominal Pressure and Hyperoxia on Portal Vein Blood Flow, Hepatocyte Proliferation and Apoptosis in a Rat Model

Abstract: Despite a significant decrease in PV blood flow, persistent IAP for 2 hours results in few changes in liver histology, and stimulates hepatocyte proliferation and apoptosis in only a few animals, supporting the presence of a recovering mechanism. Treatment with hyperoxia did not significantly change hepatocyte proliferation and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In line with this, according to some authors [36], IAH leads to visceral apoptosis. In combination with hypovolemia, however, it increased lung and liver apoptosis.…”
Section: Impact Of Hypovolemia On the Liver Kidneys And Lungssupporting
confidence: 59%
See 1 more Smart Citation
“…In line with this, according to some authors [36], IAH leads to visceral apoptosis. In combination with hypovolemia, however, it increased lung and liver apoptosis.…”
Section: Impact Of Hypovolemia On the Liver Kidneys And Lungssupporting
confidence: 59%
“…Conversely, Mogilner et al [36] found only mild liver histological alterations with an IAP of 60 mm Hg for 2 hours. These differences may be attributed to the timing of analysis (2 vs. 3 hours), as well as the method used to induce IAH (CO 2 insufflation vs. abdominal packing).…”
Section: Impact Of Hypovolemia On the Liver Kidneys And Lungsmentioning
confidence: 93%
“…Such an effect is most pronounced in the liver due to its size. Animal studies have shown that even with intraabdominal pressure of only 10 mmHg, portal venous blood flow is reduced considerably, and that at 20 mmHg, the portal venous flow and hepatic arterial flow are reduced by 35 and 55%, respectively [43]. a b Fig.…”
Section: (Recommendation 1b)mentioning
confidence: 99%
“…Specifically, the presence of IAH is known to reduce the blood flow in both the hepatic artery (HA) and the portal vein (PV), thus compromising the liver's physiological capacity to regulate its blood flow (9,18). Furthermore, along with these hemodynamic alterations, IAH has also been shown to result in varying degrees of hepatocyte necrosis, as well as impaired hepatic energy metabolism (19)(20)(21). Interestingly, however, the effects of progressively worsening IAH on liver hemodynamics and the hepatic parenchyma have not been well studied.…”
Section: Abstract Background: While Reduction Of Portal Venous (Pv) mentioning
confidence: 99%